THE INFLUENCE OF OCCUPATIONAL HEALTH AND SAFETY (OHS) AND WORK COMPETENCE ON EMPLOYEE PERFORMANCE PT. CLATEN BERSINAR SEJAHTERA - Amelia, Fitri; Soemadi, Rr Anggraini (Universitas Muhammadiyah Jakarta, 2025)
Organizational change is critical for companies to stay competitive in today's dynamic business environment. Both high-quality employee performance and strong human resource competencies are critical to a company's success. Workers' output at PT Claten Bersinar Sejahtera is the target of this research, which intends to dissect the relationship between OHS and job competences. The quantitative data analysis method was used with 80 PT Claten Bersinar Sejahtera employees as respondents. Multiple linear regression was employed for data analysis. The study's findings suggest that OHS has a positive and significant impact on employee performance, that work competence has an effect on performance, and that the combination of OHS and competence has an even stronger impact on performance. This proves that helping workers acquire new skills is crucial for improving productivity on the job. Findings from this study have significant implications for HRM practices. Keywords: Employee Performance, Occupational Health and Safety (OHS), Work Competency